Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Efektivitas Kinerja Guru di Sekolah Dasar Negeri 145 Seluma - Aprizal Syafriantoni; Adisel Adisel; Anggi Santika; Reska Norda Lesti; Siti Nabilah (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Teacher performance has not been effective, because the role of the principal's leadership has not been optimal, characterized by the principal finding it difficult to understand the nature or character of teachers and employees, so that teacher performance has not been optimal. The purpose of the study was to map and describe the leadership role of the Principal in improving the effectiveness of teacher work in Sekolah SD Negeri 145 Seluma. Using qualitative descriptive methods with a Purposive Sampling technique approach. The results showed that the principal of SDN 145 Seluma carried out his role as an educator by creating a conducive school climate and providing encouragement and advice; as managers by empowering teachers through collaboration, involving teachers in upgrading, and involving teachers in decision making; as an administrator with administrative and financial management; as a supervisor by supervising and preparing educational supervision programs; as a leader by providing instructions, increasing teacher will, and opening two-way communication; as an innovator by setting an example and developing innovative learning models; As a motivator by providing motivation to teachers, as well as regulating the physical environment and work atmosphere. So it can be concluded that the leadership role of the principal has played a role in improving employee performance, but still finds it difficult to understand the nature or character of teachers and employees, so that teacher performance has not been effective, therefore, the author can suggest, if you want to improve the effectiveness of teacher performance, then increase the leadership role of the principal as if.Keywords: Leadership Role, Principal, Teacher Work Effectiveness Abstrak: Kinerja guru belum efektif, dikarenakan peran kemimpinan kepala sekolah belum optimal, ditandai dengan kepala sekolah merasa kesulitan dalam memahami sifat atau karakter guru dan pegawai, sehingga kinerja guru belum optimal. Tujuan penelitian untuk memetakan dan mendeskripsikan peran kepemimpinan Kepala Sekolah dalam meningkatkan efektivitas kerja guru di Sekolah Dasar Negeri 145 Seluma. Menggunakan metode deskriptif kualitatif dengan pendekatan teknik Purposive Sampling. Hasil penelitian menunjukkan bahwa kepala sekolah SDN 145 Seluma melaksanakan perannya sebagai pendidik dengan menciptakan iklim sekolah yang kondusif dan memberikan dorongan dan nasehat; sebagai manajer dengan memberdayakan guru melalui kerjasama, mengikutsertakan guru dalam penataran, dan melibatkan guru dalam pengambilan keputusan; sebagai administrator dengan mengelola administrasi dan keuangan; sebagai supervisor dengan melakukan pengawasan dan penyusunan program supervisi pendidikan; sebagai pemimpin dengan memberikan petunjuk, meningkatkan kemauan guru, dan membuka komunikasi dua arah; sebagai inovator dengan memberikan teladan dan mengembangkan model pembelajaran yang inovatif; sebagai motivator dengan memberikan motivasi kepada guru, serta mengatur lingkungan fisik dan suasana kerja. Sehingga dapat disimpulkan bahwa peran kepemimpinan kepala sekolah sudah berperan dalam meningkatkan kinerja pegawai, namun masih merasa kesulitan dalam memahami sifat atau karakter guru dan pegawai, sehingga kinerja guru belum efektivitas, oleh karena itu, penulis dapat menyarankan, jika ingin meningkatkan efektivitas kinerja guru, maka tingkatkan peran kepemimpinan kepala sekolah di seolah.Kata Kunci: Peranan Kepemimpinan, Kepala Sekolah, Efektivitas Kerja Guru